Dinámicas Sociales y Roles Entre Mujeres : Percepciones en Grupos de Parentesco y Espacios Domésticos en el Oriente Antiguo. - Noria-Serrano, Beatriz (Archaeopress, 2023)
Papers in this volume aim to reevaluate the importance of women as active and powerful social agents in the definition of ancient cultures, their contribution to the economic and social development of the community and to the position, reputation, and prestige of their families.